KELUARGA DAN NEGARA: RUANG NEGOSIASI DIRI DALAM NOVEL QUI A TUí‰ MON PÈRE KARYA í‰DOUARD LOUIS - Artanti, Yeni; Burhanudin, Burhanudin (Diksi, 2021)
Abstract (Title: Family and State: Space of Self-Negotiation in "Qui A Tué Mon Père" Novel's by í‰douard Louis). Literary work reflects a culture outside its world. A family cannot be separated from society and country in which it is belonged to. Individuals in a family cannot be disconnected from their genetics. This qualitative descriptive study using Bourdieu's theoretical reference aims to describe the habitus, symbolic violence, and the arena of power in the novel "Qui a tué mon père" or "Who Killed My Father" by í‰douard Louis. The results showed that the habitus manifested through the main character "Je" or "I" was obtained through an individual historical process as someone who was born in a poor and a working family that is structurally dominated by society and state. In conclusion, the main character who experienced symbolic violence not only from his family (father and mother) but also from his social environment (neighbor, school, and government) try to negotiate his identity through this novel.   Keywords: habitus, symbolic violence, arena of power, dialectical, structural-constructivist